E-LEARNING IN HIGHER EDUCATION DURING THE PANDEMIC: A SCOPUS-BASED BIBLIOMETRIC ANALYSIS - Aarti Pushp Rawal; Madhubala A/P Bava Harji (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper presents a bibliometric analysis of scholarly articles on the convergence of e-learning during the COVID-19 pandemic. It examined diverse themes, keywords, affiliations, and sources to understand the discourse surrounding online learning during the pandemic. The dataset comprised 1,261 articles extracted from the Scopus Database. Using Biblioshiny in RStudio, a bibliometric analysis was conducted, revealing key findings. The most articles (678) related to this topic were published in 2022. The United States published the highest number of articles (715), followed by Indonesia (398) and Malaysia (267). Bradford’s Law identified Sustainability Switzerland as one of the valuable sources (87) of articles and h-index (13) publishing in this area. Universiti Teknologi Mara was one of the most prolific institutions, publishing the most articles (37). The word cloud analysis highlighted “COVID-19” as the most commonly used term (142 occurrences) in the literature. Thematic and conceptual structure maps offered an overview of the trends related to the research development in the field. The significance of this paper lies in its comprehensive analysis of scholarly articles through the application of the quantitative literature analysis method, explicitly employing bibliometric analysis. Exploring diverse themes and sources within a substantial dataset offers a deeper understanding of the evolving discourse in e-learning during a global crisis. Future studies could explore broader datasets, incorporating diverse disciplinary perspectives and information sources to enrich this evolving academic discourse.